Knife : [large type] meditations after an attempted murder - Rushdie, Salman (Random House Large Print, 2024)
Speaking out for the first time, and in unforgettable detail, about the traumatic events of August 12, 2022, Salman Rushdie answers violence with art, and reminds us of the power of words to make sense of the unthinkable. Knife is a gripping, intimate, and ultimately life-affirming meditation on life, loss, love, art-and finding the strength to stand up again.